ISLAM DAN KEBUDAYAAN MELAYU PADA ERA GLOBALISASI DI BRUNEI DARUSSALAM - Maryamah, Maryamah; Sapitri, Wira; Putri, Shabira Panca; Fatimatuzzahra, Fatimatuzzahra; Dewi, Meyana (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Brunei Darussalam is a unique country with the majority of its population being Muslim and having a rich Malay culture. In an era of globalization full of information flows and foreign cultural influences, Islam and Malay culture continue to play a central role in shaping the identity of this country. Islam is not just a religion official, but also permeated various aspects of Brunei society's life. Religious practices, moral values ??and customs based on Islam form a strong foundation in society. The magnificent mosques which are the center of religious life and the beautiful art of Arabic calligraphy are visual evidence of Islamic influence in architecture and art. Malay culture also remains alive and well. Malay is used as the official language, and many words and phrases in this language have Arabic roots. Traditional Malay art, dance, music, and clothing remains relevant in cultural events and religious celebrations.